Mega Kuningan ID FOOD Cold Chain Blueprint - Pramudiansyah, Elan (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
ID FOOD cold chain blueprint to ensure operational success and product safety, so that companies can optimize the cold chain in the form of cold warehouse or cold storage infrastructure to meet market needs and ensure quality products reach customers safely in order to fulfill beef import infrastructure requirements Brazil from the National Food Agency, where the research was carried out through a case study exploration of the ID FOOD cold warehouse located on Jl. Denpasar Raya Kav DIII Mega Kuningan South Jakarta where the research was conducted using qualitative methods using triangulation which combines document collection, in-depth interviews, and observation in collecting primary and secondary data to obtain information as a basis for determining alternative options for cold warehouse operation cooperation in the absence of allocations. budget for repairs and procurement of new equipment that will be reactivated after damage has occurred in the last 10 years and standard operational procedures in the process of handling frozen products and maintaining cold warehouses, so that the operational option for the ID FOOD Mega Kuningan Cold Warehouse in its current condition is that there is no budget in 2024 for repairs and the construction of a new cold warehouse, the operational option for operational cooperation with the Fresh Factory cold chain company partner is the right choice with a cooperation scheme to carry out building repairs, renewal of cold warehouse equipment and licensing at the responsibility of the cooperation partner, sharing of knowledge and standard operating procedures, HR training in the cold chain sector and profits Sharing product storage and inventory fulfillment.